(3eYGde GdfXe GdEOGQjI hGdbVGA aj eUQ GdaQYhfjI (B/s - (3YeQ YdGA GdOjf YeQ CMeOs; (3UHQj eMeO GdSfhSj eMeOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 2020)
(3JfGhdJ gPg GdQSGdI eYGde GdfXe GdEOGQjI hGdbVGA aj eUQ GdaQYhfjI , MjK ChQO aUdgG GdJegjOj eGgjI GdfXe GdEOGQjI hGdbVGA , hGdJYQa Ydi GdYUQ GdaQYhfj hJbSjeGJg GdeNJdaI , hJfGhd HGHgG GdChd fXGe GdMce hGdEOGQI Yf WQjb GdTQM GdeSJajV ddfXe GdEOGQjI , hPdc ef NdGd YQV fXGe GdMce hGdEOGQI , hGdeQcRjI GdEOGQjI , hVhGHW SdWGJ Gdedc , heOfjg GdOhdI GdaQYhfjI , hJfGhd SeGJ GdMce hMbhb GdTYH , hGdLgGR GdEOGQj ddOhdI , hGdehXa OGNd GdOhdI GdaQYhfjI , hWQjbg JYjjfg hMbhbg hhGLHGJg , hJCOjHg , hcPG GdCbGdje OGNd GdOhdI hcjajg EOGQJgG , hJYjjf h GNJUGUGJ MGce GdEbdje , hJfGhd HGHgG GdKGfj YQV GdbVGA hfXGeg hSeGJg , hGdbVGI hJYjjfge hMbhbge hhGLHGJge , hfXGe JCOjHge , hGdLQGFe GdeGSI HGdYOGdI , hGdfXGe GdELQGFj dfXQ GdOYhi , hELQGAGJ GdOYhi GdeOfjI hGdLfGFjI , hWQjbg JfajP GdCMcGe , GdYah Yf GdCMcGe hGdJUGdM ajgG , hJfGhd GdgjFGJ GdbVGFjI , hGdEOGQGJ GdQFjSjI hGdJGHYI GdefXheI GdbVGA , hJfGhd GdbVGA GdYGOj hGdbVGA ZjQ GdYGOj hGdbVGA GdNGU , hGdfXGe GdbGfhfj ddbVGA hVeGfGJg hGSJbdGdg , hEWGQ GdJLQje hGdYbGH aj bVGA eUQ GdaQYhfjI , YdGhI Ydi NUGFU GdfXGe GdbVGFj (B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2020.s
(3HHdjhLQGajG(B: (3UaMGJ (B318-334.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdfXe GdEOGQjIs; (3GdeQcRjI GdEOGQjI aj eUQ GdaQYhfjIs; (3fXQjI GdMb GdEdgj ddaQYhfs; (3GdSdWI GdOjfjIs; (3VhGHW SdWGJ Gdedcs; (3eOfjI GdOhdI GdaQYhfjIs; (3GdLgGR GdEOGQj ddOhdIs; (3MGce GdEbdjes; (3Gdedcs; (3eLGdS GdCYjGfs; (3fXGe GdMce GdeMdjs; (3eLdS GdYTQI GdcHGQs; (3GdbVGA aj eUQ GdaQYhfjIs; (3JCOjH GdbVGAs; (3ELQGAGJ GdJbGVj aj eUQ GdaQYhfjIs; (3ELQGAGJ GdOYhj GdLfGFjIs; (3GdeMceI GdYdjGs; (3CfhGY GdfXGe GdbVGFj aj eUQ GdaQYhfjIs; (3GdfXe GdEOGQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2020